2013
DOI: 10.1371/journal.pone.0076029
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Senescence and Identification of Differentially Expressed Genes in Tomato in Response to Monoterpene

Abstract: Monoterpenes, which are among the major components of plant essential oils, are known for their ecological roles as well for pharmaceutical properties. Geraniol, an acyclic monoterpene induces cell cycle arrest and apoptosis/senescence in various cancer cells and plants; however, the genes involved in the process and the underlying molecular mechanisms are not well understood. In this study, we demonstrate that treatment of tomato plants with geraniol results in induction of senescence due to a substantial alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 65 publications
0
20
0
Order By: Relevance
“…The SSH library was generated according to the PCR-Select cDNA Substraction kit instruction manual (Takara) as previously described (Ghosh et al, 2013). In brief, poly(A+) RNA was isolated from the total RNAs using a mRNA purification kit (Qiagen) and 2 mg of purified poly(A+) RNA was reverse transcribed using avian myeloblastosis virus reverse transcriptase.…”
Section: Construction Of the Subtraction Cdna Librarymentioning
confidence: 99%
See 1 more Smart Citation
“…The SSH library was generated according to the PCR-Select cDNA Substraction kit instruction manual (Takara) as previously described (Ghosh et al, 2013). In brief, poly(A+) RNA was isolated from the total RNAs using a mRNA purification kit (Qiagen) and 2 mg of purified poly(A+) RNA was reverse transcribed using avian myeloblastosis virus reverse transcriptase.…”
Section: Construction Of the Subtraction Cdna Librarymentioning
confidence: 99%
“…Plants synthesize and accumulate these compounds in specific tissue types perhaps for autotoxicity avoidance, because many of the secondary metabolites are known to be phytotoxic (Reigosa and Malvido-Pazos, 2007;Ghosh et al, 2013). Moreover, the sites of biosynthesis may not necessarily be the sites of storage, and long-distance transport via the xylem, phloem, or apoplast is also possible (Wink, 2010b).…”
mentioning
confidence: 99%
“…Other studies have also reported that geraniol binds and inhibits the activity of 3-hydroxy-3-methylglutaryl-CoA reductase, the enzyme that converts HMG-CoA to mevalonic acid and subsequently reduces the cell growth [64]. These reports suggest that monoterpenes, suggested that geraniol-mediated senescence involves both ethylene dependent and independent pathways [63]. Using detached lima bean leaves (Phaseoluslunatus L), [71] demonstrated that exogenous applications of the ethylene precursor, 1-aminocyclopropane-1-carboxylic acid, enhance JA-induced VTC emission.…”
Section: Stress Senescence and The Role Of Vtcsmentioning
confidence: 87%
“…Due to limited study in this area it is still unclear if VTCs serve as signal molecules at the initiation of the senescence process or a direct causal effect of senescence. [62] and in most cases, result in plant senescence [63]. Using suppression subtractive hybridization (SSH) approach, several geraniol-responsive proteins encoding genes for signal transduction, cellular metabolism, reactive oxygen species (ROS), ethylene signaling, apoptosis and DNA damage response have been reported in tomato [63].…”
Section: Stress Senescence and The Role Of Vtcsmentioning
confidence: 99%
See 1 more Smart Citation